Ta'zir (Punishment) at Islamic Boarding Schools; Between Tradition, Conception, and Shadows of Human Rights Violations: - Rahmatullah, Asep; Baharun, Segaf (Tribakti: Jurnal Pemikiran Keislaman, 2023)
This article examines the practice of Ta'zir, a form of discretionary punishment, within the context of Islamic boarding schools. Ta'zir holds a significant place in Islamic jurisprudence, allowing authorities to determine penalties for offenses not explicitly addressed in religious texts. However, the application of Ta'zir has raised concerns, particularly in the context of Islamic boarding schools, where traditional practices intersect with modern notions of human rights. Drawing upon a multi-disciplinary approach, this study delves into the historical, cultural, and religious aspects of Ta'zir, elucidating its evolution from its inception to its current manifestations within Islamic boarding schools. By analyzing primary sources, legal texts, and case studies, the article underscores the diverse interpretations of Ta'zir and its malleability in adapting to contemporary circumstances. Furthermore, the article critically evaluates the potential conflicts between the traditional practice of Ta'zir and international human rights standards. It examines instances where Ta'zir punishments might be perceived as infringing upon human dignity, bodily integrity, and freedom from cruel, inhuman, or degrading treatment. The study also explores the role of Islamic boarding schools in shaping and perpetuating these practices, considering the interplay between religious education, discipline, and the protection of children's rights. The findings of this research reveal a complex landscape where tradition clashes with modern sensibilities. The article advocates for a nuanced dialogue between religious scholars, educators, and human rights advocates to strike a balance between preserving cultural heritage and upholding universally recognized human rights. It highlights the importance of reinterpretation and contextualization of Ta'zir in line with the principles of justice, mercy, and human dignity as emphasized within Islamic teachings. In conclusion, this article contributes to the ongoing discourse on the compatibility of traditional Islamic practices with contemporary human rights frameworks. It calls for a thoughtful reevaluation of Ta'zir within Islamic boarding schools, promoting an inclusive approach that safeguards both religious heritage and fundamental human rights.